UTILIZATION OF CHATGPT IN THE PRODUCTION PROCESS OF JOURNALIST NEWS IN THE MIMBAR UMUM MEDAN NEWSPAPER - Fitri Aulia; Erwan Effendi (Journal Analytica Islamica, 2026)
The development of generative artificial intelligence (AI) is beginning to transform news production practices, including in local print media. This study aims to analyze the use of ChatGPT in the news production process at the Mimbar Umum Medan newspaper, while also examining journalists' perceptions of its use and its implications for journalistic professionalism and ethics. The study employed a qualitative approach with a case study method through in-depth interviews, observations of editorial workflows, and documentation studies. The research findings indicate that ChatGPT is used limitedly as a technical tool, primarily for generating news ideas, composing initial drafts, refining language, and summarizing supporting documents. The novelty of this study lies in the finding that in the context of local media, the use of ChatGPT has not led to editorial automation, but rather to a pattern of augmented journalism that still places journalists and editors as the primary controllers of editorial decisions. On the one hand, this use improves work efficiency and manuscript readability. On the other hand, there are risks of inaccuracy, information bias, and technological dependency if not accompanied by rigorous verification. Thus, ChatGPT functions more as a supporting instrument than a replacement for human journalistic work.